Crystal structure of Ba(2)Co(BO(3))(2) - N’Faoui, Fatima-Ezahra (International Union of Crystallography, 2019)

(untitled) (Acta Crystallogr E Crystallogr Commun)
Single crystals of dibarium cobalt(II) bis(orthoborate), Ba(2)Co(BO(3))(2), have been obtained from the melt. The crystal structure is composed of two isolated (BO(3))(3−) triangles linked to Co(2+) cations. The resulting [CoO(5)] square pyramids and the borate anions make up branched rows extending parallel to [010]. The barium cations occupy two sites in the voids of this arrangement and exhibit coordination numbers of nine each. A comparison with the structures of other A (2) M(BO(3))(2) compounds reveals a unique five-coordination of the small metal M in the title compound instead of four- or six-coordination for the other A (2) M(BO(3))(2) compounds with M = Cu, Zn, Mg, Ca, or Cd.